Potensi Kombinasi Mikrosfer Fukoidan dan MiRNA-200b sebagai Terapi pada Kanker Payudara Kemoresisten - Sinta Wiranata; Made VW Yani; Agung Bagus S Satyarsa; I Ketut R Ardiana; Putu AT Adiputra (Journal of Medicine and Health, 2020)
Breast cancer still become a major health problem in Indonesia and worldwide until today. Based on WHO 2012, breast cancer incidence is reported as 1.67 million cases with 90% of mortality rate in the metastasis stage. Chemoresistant is one cause of this increased mortality and morbidity. Nowadays, there are many treatment choices for cancer, but 90% incident of chemoresistant breast cancer occur even with prior chemotherapy. This review aimed to describe the potential of microsphere combinations fucoidan and miRNA-200b as a treatment for chemoresistant in breast cancer. Literature review were derived from scientific journals using www.pubmed.com and scholar.google.com database with “chemoresistant breast cancer, Fucoidan, microRNA-200b” as keyword. Fucoidan can induce apoptosis through the extrinsic pathway involving apoptotic receptor, or intrinsic pathway involving changes in mitochondrial membrane potential (MMP) to release cytochrome C and activating the apoptotic signal. Meanwhile, miRNA-200b expression, will decrease Sp1 expression and decrease histone-3 acetylation level in a miRNA-200b promoter, resulting in decreased cancer cell migration and invasion. However, no studies have evaluated this combination clinically. So, further studies are needed to confirm the potential of microsphere combination fucoidan and miRNA-200b in chemoresistant breast cancer. Keywords: chemoresistant breast cancer; Fucoidan; miRNA-200b.